2015
DOI: 10.1002/stem.2038
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Factors Released by Megakaryocytes Thrombin Cleave Osteopontin to Negatively Regulate Hematopoietic Stem Cells

Abstract: Factor V (FV) and factor X (FX) activate and complex to form prothrombinase which subsequently cleaves prothrombin (PT), converting it to active thrombin. Thrombin cleaved osteopontin (tcOPN) contains a cryptic binding site for a 4 b 1 and a 9 b 1 integrins. We have previously shown that hematopoietic stem cells (HSC) bind to tcOPN via this site resulting in a decrease in their proliferation and differentiation. Therefore, tcOPN and the factors required for its generation are important components of the HSC ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 28 publications
(39 reference statements)
0
28
0
1
Order By: Relevance
“…The functional characteristics of the endosteal BM have been a topic of great interest since the concept of a stem cell niche was originally postulated by Schofield 50 . Studies highlighted the endosteal niche as a hypoxic environment 51 where cells such as osteoblasts 52,53 , endothelial cells 54 , perivascular cells 12 , megakaryocytes 55 as well as their associated ECM proteins are important regulators of HSC maintenance and function. Herein, we show HSC and progenitors isolated from the endosteal region express a 9 b 1 /a 4 b 1 that are in a higher affinity, ligand-primed binding conformation relative to cells from the central compartment.…”
Section: Discussionmentioning
confidence: 99%
“…The functional characteristics of the endosteal BM have been a topic of great interest since the concept of a stem cell niche was originally postulated by Schofield 50 . Studies highlighted the endosteal niche as a hypoxic environment 51 where cells such as osteoblasts 52,53 , endothelial cells 54 , perivascular cells 12 , megakaryocytes 55 as well as their associated ECM proteins are important regulators of HSC maintenance and function. Herein, we show HSC and progenitors isolated from the endosteal region express a 9 b 1 /a 4 b 1 that are in a higher affinity, ligand-primed binding conformation relative to cells from the central compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, megakaryocytes, which have been shown to influence HSC biology both directly and indirectly, are a source of thrombin, which has been shown to promote fibronectin secretion by human BM mesenchymal stem cells via PAR-1 and PAR-2 mediated ERK signaling [Heazlewood et al, 2013;Chen et al, 2014;Storan et al, 2015]. Megakaryocyte released thrombin has also been demonstrated to cleave full-length osteopontin [Storan et al, 2015].…”
Section: Extracellular Matrix Moleculesmentioning
confidence: 99%
“…HPSCs bind circulating OPN, which results in a decrease in their differentiation and proliferation. (43,44) We have previously shown that serum OPN levels increase in ALD. (18) The increased cellularity observed in Opn 2/2 mice along with HPSC mobilization and hepatosplenomegaly suggest that OPN plays a prominent role in HPSC niche interactions.…”
Section: Discussionmentioning
confidence: 98%
“…It is at present an unrecognized component of endosteally located stem cell niches with an important physiologic role in the regulation of HPSC localization and proliferation. HPSCs bind circulating OPN, which results in a decrease in their differentiation and proliferation . We have previously shown that serum OPN levels increase in ALD .…”
Section: Discussionmentioning
confidence: 99%